Social Policy Review 23 : Analysis and Debate in Social Policy, 2011 - Holden, Chris (Book collections on Project MUSE., 2011)
This edition of Social Policy Review presents an extensive analysis of the coalition government's social policies and is essential reading for social policy academics and students and for anyone who is interested in the implications of government policy.